Set operation with MAPLE and embedded components - M. Ariffin, Latifah; Kilicman, Adem (Elsevier, 2010)
Embedded components in MapleTM 10 enable us to embed simple graphical interface components for example, a button, in our document. These components could then be associated with actions that are to be executed. A text field could also be a part of an input equation. We could embed Button, Toggle Button, Combo Box, Check Box, List Box, Text Area, Label, Slider, Plot and Function. This latest feature has similarity as Maplet which previously introduced in Maple 8. The significant difference between these two Maple components is Maplet could be view with Maplet Viewer without having to launch a Maple session where as for the Embedded Components; it could only be view with a launched Maple session. In this talk, we’ll see how the SET OPERATIONS window were build and discuss on its ability to increase the user motivations towards learning this topic.